Biometry of the calcaneocuboid joint - Assi, C. (2013)
Precise biometric data of calcaneus, cuboid bones and calcaneocuboid joint are not alluded to in textbooks of anatomy. This study focussed on the biometry of 50 calcanei, 30 cuboid dry bones, and anatomical specimens of 21 transverse tarsal joints. Measurement of the length, width, angular orientation, contact surface and radius of curvature, rolling band of the joints surfaces according to the main axes were performed. The results focussed on biometric variations with several morphological types never identified previously. Measurements obtained on dry bones and anatomical specimens with the functions of ligaments were distinguished. The morphology of the calcaneus could explain the results of osteotomy procedures for the treatment of adult flatfoot. A better knowledge of the joint surfaces and biometric data would generate a modeling of the calcaneocuboid joint and function in locking the transverse tarsal joint.